KLAIM TANAH MELAWAN HUKUM DALAM PENGADAAN TANAH PERLUASAN BANDARA SOEKARNO-HATTA: STUDI KASUS PUTUSAN PENGADILAN NEGERI TANGERANG DAN PENGADILAN TINGGI BANTEN - Hannandi, Abdill; Yamin, Muhammad; Suprayitno, Suprayitno (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
Several factors contribute to issues in providing compensation for land acquisition, often resulting in lengthy and prolonged processes. In addition to compensation-related problems, land ownership disputes often arise during the acquisition process. This research addresses the mechanism for providing compensation for land acquisition in cases of ownership disputes, based on justice and legal certainty. It also examines the legal protection for landowners in cases of unlawful ownership claims related to land acquisition compensation and analyzes the judge's decision regarding Tangerang District Court Decision No. 577/Pdt.G/2020/PN.Tng in conjunction with Banten High Court Decision No. 241/PDT/2021/PT.BTN. This study employs a normative juridical method, referring to legal norms through literature review to obtain secondary data. It is descriptive and analytical in nature, using qualitative analysis for data interpretation. The study found that compensation for land acquisition in cases of ownership disputes, such as in Case No. 577/Pdt.G/2020/PN.Tng, is entrusted to the court. Preventive legal protection for landowners in the event of ownership claims is provided through ownership evidence. If this evidence is insufficient, the aggrieved party may file a lawsuit. The judge’s decision in this case was based on legal considerations and the evidence presented. The research recommends that parties harmed by unlawful land ownership claims in land acquisition cases seek legal recourse through the court.